شیخِ طریقت سے عقیدت میں مطلوب رویہ : "طریقۂ محمدیہ" کا مطالعہRequired Attitude in Devotion to a Sufi Sheikh: A Study of "Tareeqa-e-Muhammadia " (Al-Qamar, 2021)
In Sufism, Sheikh or Murshid has fundamental importance. A perfect Sheikh is one whose chain of allegiance is valid up to the Messenger of Allah; who have spent a lifetime in austerities and worship. The Sheikh guides his disciples and brings them closer to God.  Over time, this notion of Sufi Sheikh declined and many faults arose in this regard. This corrupted concept of Sheikh was tried to be improved by different scholars and Sufis. In Indo-Pak subcontinent, the most prominent of these personalities is the famous revivalist Syed Ahmad Shaheed (1786-1831). He introduced "Tareeqa-e-Muhammadia" in Sufism, the aim of which was to reform the innovations and “Bidʻāt” in Sufism. Syed Ahmad believed that the first source of guidance was Quran and Sunnah. If a Sheikh does something contrary to Quran and Sunnah, he should be stopped immediately. This paper presents a study of the thoughts and ideas of Syed Ahmad Shaheed on devotion to a Sufi Sheikh. It starts with the exaggerated ideas of Sufism in terms of devotion to Sheikh, and then presents the ​​reforming thoughts of Syed Ahmad’s “Tareeqa-e-Muhammadia”. The primary purpose of the movement of “Tareeqa-e-Muhammadia” was to make Muslims committed and practicing Muslims. “Tareeqa-e-Muhammadia” negates all types of Shirk with Allah Almighty. Syed Ahmad waged a jihad to rid Sufism of the influence of Hindu ideologies, in which a Sufi Sheikh attains the status of a deity. To seek help and guidance from prophets, saints, imams etc. was declared against “Aqīda-e-Tawhīd”.
Keywords: Syed Ahmed Shaheed; Tareeqa – e – Muhammadia; ‘Aqeeda e Tauheed’